Elementary operations: a novel concept for source-level timing estimation. (2nd January 2019) - Frid, Nikolina; Ivošević, Danko; Sruk, Vlado
ABSTRACT: Early application timing estimation is essential in decision making during design space exploration of heterogeneous embedded systems in terms of hardware platform dimensioning and component selection. The decisions which have the impact on project duration and cost must be made before a platform prototype is available and software code is ready to be linked and thus timing estimation must be done using high-level models and simulators. Because of the ever increasing need to shorten the time to market, reducing the amount of time required to obtain the results is as important as achieving high estimation accuracy. In this paper, we propose a novel approach to source-level timing estimation with the aim to close the speed-accuracy gap by raising the level of abstraction and improving result reusability. We introduce a concept – elementary operations as distinct parts of source code which enable capturing platform behaviour without having the exact model of the processor pipeline, cache etc. We also present a timing estimation method which relies on elementary operations to craft hardware profiling benchmark and to build application and platform profiles. Experiments show an average estimation error of 5%, with maximum below 16%.